Des pas sur la neige: Technique-Compositional Aspects of the Prelude by Caude Debussy - Sergio Molina (Opus, 2011)
This work analyzes compositional techniques used on Prelude No 6/I, Des pas sur la neige, by Claude Debussy. It discusses an establishment of the form based on variation processes arising from interrelationship between compound and stratified textures, taking the characteristic ostinato of the piece as a reference point. In this context, axis of symmetry that regulates overlapping and centricity are identified. At the conclusion is emphasized the narrative of the post-tonal speech by Debussy – expressed at the variety of different approaches of the ostinato, used as a familiar material and point of intersection between different sets and centricities.